2014
DOI: 10.4103/0972-5229.142175
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and outcome of acute lung injury and acute respiratory distress syndrome in the surgical intensive care unit

Abstract: Introduction:To determine the incidence and mortality of acute lung injury (ALI) and acute respiratory distress syndrome (ARDS) in a cohort of patients with risk factors admitted to the Surgical Intensive Care Unit (SICU).Materials and Methods:A prospective observational inception cohort study with no intervention was conducted over 12 months. All patients with at least one known risk factor for ALI/ARDS admitted to the SICU were included in the study. The APACHE II severity of disease classification system sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 22 publications
3
27
1
2
Order By: Relevance
“…10,11,15 Sepsis continues to be the leading cause of ARDS and is often associated with tropical illnesses, including malaria, leptospirosis, dengue, etc., seen in a predominantly male population with occupational exposure to unsanitary environmental conditions. 10,11,15,16 Consistent with these studies, 10,11,16 our patients too showed similar demographic and etiological characteristics, but the microbiological yield of our patients was significantly lesser (17.9%) vs. the 40-50% range noted by our Indian colleagues. This can partially be explained by the nature of patients presenting to our tertiary referral center who have often times been admitted at other centers and received multiple doses of antimicrobials.…”
Section: 2supporting
confidence: 78%
See 1 more Smart Citation
“…10,11,15 Sepsis continues to be the leading cause of ARDS and is often associated with tropical illnesses, including malaria, leptospirosis, dengue, etc., seen in a predominantly male population with occupational exposure to unsanitary environmental conditions. 10,11,15,16 Consistent with these studies, 10,11,16 our patients too showed similar demographic and etiological characteristics, but the microbiological yield of our patients was significantly lesser (17.9%) vs. the 40-50% range noted by our Indian colleagues. This can partially be explained by the nature of patients presenting to our tertiary referral center who have often times been admitted at other centers and received multiple doses of antimicrobials.…”
Section: 2supporting
confidence: 78%
“…This can partially be explained by the nature of patients presenting to our tertiary referral center who have often times been admitted at other centers and received multiple doses of antimicrobials. The mortality in our patients was 53.7%, which, despite being comparable to other Indian studies, 10,11,[15][16][17] is significantly higher than the 15-30% noted in Western literature. 2,5 Our study had certain limitations as well.…”
Section: 2contrasting
confidence: 44%
“…Population structure, burden of disease, and risk factors for ARDS might differ between the developed and developing countries. Singh et al [10] performed a prospective observational study to examine the prevalence of ARDS, as defined by the AECC criteria, in patients admitted during a 12-month period in a surgical ICU of a large tertiary care hospital in India. From a total of 902 admissions, they identified 67 (7.4%) patients meeting the AECC criteria for ARDS.…”
Section: Population-based Incidence Of the Acute Respiratory Distressmentioning
confidence: 99%
“…Такі пацієнти мають вищий рівень ле-тальності (30-60 %) порівняно з хворими, в яких є інші причини розвитку ГРДС (рівень летальності не перевищує 30 %) [2,3]. Важливою є рання іден-тифікація пацієнтів із ризиком виникнення ГРДС.…”
Section: результати та обговоренняunclassified
“…Аналізуючи міжнародні дослідження, можна ви-окремити певні біохімічні показники, що вірогідно вирізняються у тих пацієнтів із сепсисом, в яких у подальшому розвинеться ГРДС. Зокрема, при над-ходженні до лікарні у таких хворих є вищий рівень поліорганної дисфункції та paCO 2 , нижчий рівень pH порівняно з тими, в кого не було ураження ле-гень [2]. ГРДС є гетерогенним синдромом, домінуючу роль у розвитку якого відіграє ушкодження аль-веоло-капілярної мембрани та підвищення її про-никності [1].…”
Section: результати та обговоренняunclassified